2018
DOI: 10.1111/epi.14456
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel: Does it have broad‐spectrum potential?

Abstract: This article reviews the profile of perampanel, a novel noncompetitive α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate (AMPA) receptor antagonist, and its role as a potential broad-spectrum antiepileptic drug in the treatment of epilepsy. For this narrative review, data were collected using specified search criteria. Articles reporting the evidence for perampanel's efficacy from preclinical models, phase 3 clinical studies, observational studies, and descriptive evidence were included. AMPA receptors play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 109 publications
3
49
0
Order By: Relevance
“…Perampanel is a new-generation and widely prescribed anticonvulsant and is well known for its non-competitive antagonist action at AMPA receptors (Hanada et al, 2011;Potschka & Trinka, 2019 AMPA antagonist 1-(4-aminophenyl)-3-methylcarbamyl-4-methyl-3, 4-dihydro-7,8-methylenedioxy-5H-2,3-benzodiazepine hydrochloride (GYKI-53655), which shares the binding site of perampanel (Hanada et al, 2011), was found to be superior to that of the competitive AMPA antagonist 2,3-dioxo-6-nitro-1,2,3,4-tetrahydrobenzo[f]quinoxaline-7-sulfonamide (NBQX) in experimental seizure models (Yamaguchi, Donevan, & Rogawski, 1993). On the other hand, the binding affinity of perampanel could be much lower than that of CNQX (Chen et al, 2014;Honoré, Drejer, Nielsen, & Nielsen, 1989;Johansen et al, 1993).…”
Section: Perampanel Work As Modifier Of Reverberating Discharges Fmentioning
confidence: 99%
“…Perampanel is a new-generation and widely prescribed anticonvulsant and is well known for its non-competitive antagonist action at AMPA receptors (Hanada et al, 2011;Potschka & Trinka, 2019 AMPA antagonist 1-(4-aminophenyl)-3-methylcarbamyl-4-methyl-3, 4-dihydro-7,8-methylenedioxy-5H-2,3-benzodiazepine hydrochloride (GYKI-53655), which shares the binding site of perampanel (Hanada et al, 2011), was found to be superior to that of the competitive AMPA antagonist 2,3-dioxo-6-nitro-1,2,3,4-tetrahydrobenzo[f]quinoxaline-7-sulfonamide (NBQX) in experimental seizure models (Yamaguchi, Donevan, & Rogawski, 1993). On the other hand, the binding affinity of perampanel could be much lower than that of CNQX (Chen et al, 2014;Honoré, Drejer, Nielsen, & Nielsen, 1989;Johansen et al, 1993).…”
Section: Perampanel Work As Modifier Of Reverberating Discharges Fmentioning
confidence: 99%
“…PER has been demonstrated to reduce neuronal excitation primarily through the blockade of AMPA receptors [1,2,3]. As a once-daily oral AED, it has been approved globally for the adjunctive treatment of partial epilepsy and primary generalized tonic-clonic seizures [4,5,6], although the underlying mechanism of actions through which PER exerts its broad-spectrum antiepileptic effect has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A low dose of perampanel was remarkably effective for myoclonic seizures in our patient. Perampanel, a third-generation anti-epileptic drug, is a noncompetitive alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor antagonist that is highly effective as an adjuvant therapy in patients with generalized and focal epilepsy [ 7 ]. Furthermore, perampanel was newly approved as monotherapy for focal epilepsy in Japan in January 2020 [ 8 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%